Strategies and planning to mitigate the effects of climate change in children’s outdoor playing environments - Lundgreen,Eva; Karaba Bäckström,Martin (2023)
Background: Children’s need for play is intertwined with health and development. For many children public playgrounds represent environments that are playful and important in developing good health. Without efforts to facilitate climate adaptation of outdoor playgrounds there may be a loss of health and well-being during childhood and their future lives. Purpose: To explore the reasoning and described strategies among professionals responsible for development, plannings and solutions concerning outdoor playing grounds within the perspective of possible climate changes and with a special focus on play value. Method: A cross-sectional design with a qualitative inductive approach to describe data around the knowledge and planning from professionals working in the field. Eight semi-structured interviews were held and analysed with manifest content analysis. Results: Through the eight conducted interviews four themes with supporting categories emerged; a new design paradigm for outdoor playing environments, a need for updated regulation- and security guidelines for outdoor playing environments, nature based playing environments are more climate change resilient, maintenance and construction of nature based outdoor playing environments. Conclusions: Increasing the amount of nature and ecosystem services in outdoor playing environments supports resilience against climate change effects, increases play value and playing activities with high levels of physical activity and contributes to doing occupational justice through ecopation.
Keywords: Outdoor play; climate adaptation; child development; occupational justice; usability and accessibility